CONNECTION BETWEEN BEER BRANDS AND CONSUMERS: the importance of communications to establish a deeper relationship with the public - Fávero de Souza, Helena; del Vechio, Gustavo Henrique (Revista Interface Tecnológica, 2020)
The image and meanings of a brand are built through the interaction of the public with each of its contact points, which includes not only advertisements, but also experiences in stores, consumption of products, interaction at events, investment in social causes and more. Put in this way, this study seeks to assess the importance of communications for beer brands, verifying whether consumers are influenced by their actions and, therefore, relate more deeply to them. In the theoretical foundation, it presents the importance of communications, demonstrating that advertising is not the only resource to connect to the public and establish a good brand image. Then, in order to verify the concepts studied, it proposes a qualitative research, through in-depth interviews with consumers of three popular beers in Brazil, which are Brahma, Heineken and Corona, in order to assess whether they are impacted by the actions and communications of these brands. What can be seen from this study is that the more brands invest in communication, actions and experiences, the more they can win the preference of individuals, who not only consume their products, but prefer them for the values ​​they express and defend.
Keywords: Beer Brands; Communication; Branding Management; Relationship